Neurotrophin Receptor Activation and Expression in Human Postmortem Brain: Effect of Suicide - Dwivedi, Yogesh; Rizavi, Hooriyah S.; Zhang, Hui; Mondal, Amal C.; Roberts, Rosalinda C.; Conley, Robert R.; Pandey, Ghanshyam N. (Biological psychiatry (1969), 2009)
The physiological functions of neurotrophins occur through binding to two receptors: pan75 neurotrophin receptor (p75 NTR) and a family of tropomyosin receptor kinases (Trks A, B, and C). We recently reported that expression of neurotrophins and TrkB were reduced in brains of suicide subjects. This study examines whether expression and activation of Trk receptors and expression of p75 NTR are altered in brain of these subjects. Expression levels of TrkA, B, C, and of p75 NTR were measured by quantitative reverse transcription polymerase chain reaction and Western blot in prefrontal cortex (PFC) and hippocampus of suicide and normal control subjects. The activation of Trks was determined by immunoprecipitation followed by Western blotting using phosphotyrosine antibody. In hippocampus, lower mRNA levels of TrkA and TrkC were observed in suicide subjects. In the PFC, the mRNA level of TrkA was decreased, without any change in TrkC. However, the mRNA level of p75 NTR was increased in both PFC and hippocampus. Immunolabeling studies showed similar results as observed for the mRNAs. In addition, phosphorylation of all Trks was decreased in hippocampus, but in PFC, decreased phosphorylation was noted only for TrkA and B. Increased expression ratios of p75 NTR to Trks were also observed in PFC and hippocampus of suicide subjects. Our results suggest not only reduced functioning of Trks in brains of suicide subjects but also that increased ratios of p75 NTR to Trks indicate possible activation of pathways that are apoptotic in nature. These findings may be crucial in the pathophysiology of suicide.